Career motivations for postgraduate study enrollment in institutions of higher learning / Yusnida Yusof - Yusof, Yusnida (2015)
The main objective of this dissertation is to examine the levels of their perception on career motivation , personal needs, personal attributions, organizational development, program attracti veness, and reward for postgraduate study enrollment in institution s of higher learning, to identify the most prominent variables that may influence the career motivation for postgrad uate study enrollment in institutions of higher learning, to examine the relationship between personal needs, personal attributions, organizational development, program attractiveness and reward with career moti vations for postgraduate study enrollment in institution s of higher learning and to investigate the differences between several selected profile (gender, age, position , university, education, mode of study and salary) that are related to career motivations for postgraduate study enrollment in institutions of higher learning. This study involves 330 samples from three (3) Universities which are University Teknologi Mara Terengganu (UiTMT), U niversity Malaysia Terengganu (UMT), and University Sultan Zainal Abidi n (UniSZA). 330 Set of questionnai re have been distributed to collect data and the data was analyzed by using the SPSS Windows Version 20. Analysis of 330 responses using Pearson Correlation analysis revealed that there is a significant relationship between organization development passion and career motivations. From the finding, an organization development as a higher value that is 0.560, and it showed that organization development is the best pred ictor, followed by personal attributions, personal needs, program attractiveness, and reward that can be used to predict career motivations for postgrad uate study enrollment. Here were some limitations that have been identified underlying i n this research invest igated. From the research limitation described , it is proposed that future research to be carried out in order to cover the research area more thoroughly